2017
DOI: 10.1097/sih.0000000000000248
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Evaluation of the Effects of Patient Load on Mental Workload of Healthcare Staff

Abstract: Based on this study, the researchers found that the modeled inpatient unit can safely handle the expected patient load increases. The study provides the unit with information to proactively prepare and reduce healthcare staff overloading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…By using DES to evaluate different scenarios, they quantitatively demonstrated that advanced preparation has the strongest potential for improving patient waiting times [32]. In addition, Rusnock et al (2017) used DES to quantitatively model the mental workload of healthcare staff in an inpatient unit at a medical center [33]. The model was deployed to find the optimal idle time, average workload, and overload time of healthcare staff under different patient loads.…”
Section: Plos Onementioning
confidence: 99%
“…By using DES to evaluate different scenarios, they quantitatively demonstrated that advanced preparation has the strongest potential for improving patient waiting times [32]. In addition, Rusnock et al (2017) used DES to quantitatively model the mental workload of healthcare staff in an inpatient unit at a medical center [33]. The model was deployed to find the optimal idle time, average workload, and overload time of healthcare staff under different patient loads.…”
Section: Plos Onementioning
confidence: 99%
“…Así mismo, los autores analizados coinciden en reafirmar que la carga mental es una construcción compleja, con múltiples dimensiones (8,18), que involucra: aspectos o demandas cognitivas y características de las tareas; situación y capacidad de las personas para procesar información y tomar decisiones para cumplir con las demandas físicas, temporales y ambientales (18); carga externa que incluye la carga cognitiva causada por el exceso de información o actividad (8); relación percibida entre la capacidad de recursos mentales y de procesamiento de información con procesos neurofisiológicos, perceptuales y cognitivos requeridos para realizar una tarea (19); esfuerzo cognitivo en un tiempo concreto para hacer frente a tareas (20); relación entre la información procesada y las dificultades para tomar decisiones bajo presión temporal; carga atencional necesaria para mantener un nivel de ejecución adecuado (10); desequilibrio entre las demandas de la tarea, las habilidades y características de los trabajadores (10,21).…”
Section: Categorías De Análisisunclassified
“…1,2 Studies of anesthesiologists, obstetricians, and internists have demonstrated the utility of simulation-based CPD (SBCPD) to improve decision making and test protocols. [3][4][5] Cook et al 6 similarly explored the outcomes of SBCPD, concluding that physician participation has a positive impact on knowledge, skills, and behaviors with a significant improvement in patient-related outcomes. A recent systematic review of SBCPD articles demonstrated extensive variability in design, delivery, and evaluation of simulation across specialties, with several of the included studies highlighting the positive impact of simulation-based education (SBE) on physician learning and organizational performance.…”
mentioning
confidence: 99%
“…Simulation is becoming a popular educational modality for physician continuing professional development (CPD), with demands for its increased utilization 1,2 . Studies of anesthesiologists, obstetricians, and internists have demonstrated the utility of simulation-based CPD (SBCPD) to improve decision making and test protocols 3–5 . Cook et al 6 similarly explored the outcomes of SBCPD, concluding that physician participation has a positive impact on knowledge, skills, and behaviors with a significant improvement in patient-related outcomes.…”
mentioning
confidence: 99%